Buleleng Healthy And Social Care Home For The Elderly With Organic Neo Vernacular Approach (terlambat mengumpulkan) - Bernadette Saminoe (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2023)
Indonesia has plunged into an aging society, and according to Indonesian statistics, Bali ranks fourth in the ranking of the largest elderly population, but in contrast, the quantity of elderly accommodation in Indonesia, especially in Bali can be considered as very low. Therefore, in this project, a redesign will be carried out for the purpose of remodeling elder society. Creating an inclusive comfortable building dedicated to the elderly by improving the residents well-being through sensory and wellness design and neo vernacular architecture